2021
DOI: 10.3389/fpls.2021.678830
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Differentially Influences the Capacity of Trichoderma Species to Induce Plant Defense Responses in Tomato Against Insect Pests

Abstract: Species of the ecological opportunistic, avirulent fungus, Trichoderma are widely used in agriculture for their ability to protect crops from the attack of pathogenic fungi and for plant growth promotion activity. Recently, it has been shown that they may also have complementary properties that enhance plant defense barriers against insects. However, the use of these fungi is somewhat undermined by their variable level of biocontrol activity, which is influenced by environmental conditions. Understanding the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 69 publications
(103 reference statements)
3
36
0
Order By: Relevance
“…However, it should be mentioned that the biocontrol efficacy of pathogens and/or pests plus the plant benefits observed in this study may be influenced by the controlled conditions imposed in the experimental design. In fact, abiotic factors, such as temperature, have been noted to significantly affect the important favorable characteristics of diverse strains of Trichoderma tested as the biological control agents as well as their culturability [86]. The next phase in the present BM selection process should involve testing in the field, in the "real-world" cultivation environment to determine if the selected isolates maintain their capacity as useful agricultural products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be mentioned that the biocontrol efficacy of pathogens and/or pests plus the plant benefits observed in this study may be influenced by the controlled conditions imposed in the experimental design. In fact, abiotic factors, such as temperature, have been noted to significantly affect the important favorable characteristics of diverse strains of Trichoderma tested as the biological control agents as well as their culturability [86]. The next phase in the present BM selection process should involve testing in the field, in the "real-world" cultivation environment to determine if the selected isolates maintain their capacity as useful agricultural products.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another mechanism that several authors reported is once again ISR in which the endophyte induces the activation of plant defenses that suppress insects [14,40]. As evidenced by a recent study, the resistance of tomato plants root-colonized by Trichoderma against M. euphorbiae is related to an increase of plant endogenous defense processes attested by the up-regulation of the transcripts coding for ET, JA, SA, and PR proteins that are likely responsible for a primed state of the plants, as described for ISR and SAR [86]. It can be hypothesized that a similar mechanism underlies the biocontrol effect that was observed in B. bassiana-colonized plants, but further investigation need to be undertaken to shed light on this important aspect.…”
Section: B Bassianamentioning
confidence: 91%
See 1 more Smart Citation
“…Colonization by Trichoderma spp. (Sordariomycetes, Hypocreaceae) induces the systemic defense response of plants against aphids [30,32,33] and Lepidoptera [32,34], and attracts both parasitoids [35] and predators [36]. Endophytic B. bassiana can control different species of aphids on a series of crops [37][38][39] and negatively affects the fitness of several Lepidoptera species [40][41][42][43][44], even if further investigations are required for more thoroughly understanding the mechanism of action.…”
Section: Plant-mediated Interactionsmentioning
confidence: 99%
“…Moreover, another experiment showed that temperature and moisture levels could be used to make good predictions for effective biocontrol using Trichoderma among other BCAs against Botrytis cinerea in grape berries [33]. Moreover, an increase of 5 • C can significantly influence the response of Trichoderma in relation to the induction of the plant response in tomato plants [34]. All these environmental factors and the alteration in temperatures due to climate change [35] represent major challenges in wine production.…”
Section: Introductionmentioning
confidence: 99%